Europa 2005-2011: gli sviluppi istituzionali dell’Ue visti da Washington - Caccamo, Domenico (Rivista di studi politici internazionali, 2022)
This essay esamines a segment of the European integration process, characterized by a substantial acceleration of the institutional development within the Union framework. A first achievement was represented by the Refom Treaty signed in December 2007, a second by the Fiscal Pact negotiated in December 2011. In the same period various projects entered in competition, aimed at the European energy security: the decline of the Nabucco project, originally sustained by the Usa, was compensated by the opening of the first section of North Stream, agreed upon by Russia and Germany. The whole period 2005-2011 was marked by French-German solidarity, under the dual leadership Merkel-Sarkozy. American diplomacy considered suspicuiously these developments in the European integration, which threatened to weaken the Western system in its Eastern Atlantic pillar and to confirm the transition to a multipolar world. The American press took different positions: the «Christian Science Monitor» was sensitive to European motivations, while the «Wall Street Journal» was openly hostile.